Analysis of Embryo Transfer Pregnancy Rate from Friesian Holstein Cow Recipients in BET Cipelang - Syahdan, Roshif; Atabany, Afton; Komala, Iyep; Ningtias, Putri Indah (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Indonesia has significant potential in the beef and dairy cattle sectors but faces challenges in improving the genetic quality of livestock. Embryo transfer is a biotechnology that can enhance genetic quality and livestock productivity. This study aims to examine and analyze the factors affecting the success rate of pregnancies in FH dairy cattle as recipients of embryo transfer at BET Cipelang. Secondary data from BET Cipelang (2017-2023) were used, including embryo quality, transfer methods, recipient age, estrus synchronization methods, and embryo donor breeds. The results showed that good embryo quality (24.55%) and fresh transfer methods (35.19%) significantly increased pregnancy success (p < 0.05). Synchronization methods using PGF2α and a combination of Progesterone + PGF2α increased the chances of pregnancy by 3.60 and 3.89 times, respectively, compared to natural estrus. Although not statistically significant, the age groups of 3-5 years and 6-9 years had higher chances of pregnancy compared to the 10-12 years age group. The donor breed of embryos did not show a significant difference in pregnancy rates. This study highlights the importance of focusing on embryo quality and transfer methods to improve embryo transfer success rates.